2017
DOI: 10.33588/fem.202.878
|View full text |Cite
|
Sign up to set email alerts
|

Experimentar empatía en estudiantes de medicina: deprivación sensorial

Abstract: Experiencing empathy in medical students: sensorial deprivation Aim. To identify emotions experienced by medical students in a workshop of sensory deprivation to enhance empathy. Subjects and methods. The workshop program (visual deprivation, auditory deprivation and physical disabilities) is presented. Emotions are identifi ed and measured by Self-Assessment Manikin scale. Medical empathy is measured by Jeff erson Scale of Physician Empathy. Results and conclusions. Sensory deprivation can experience diff ere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
0
2
0
2
Order By: Relevance
“…It is worth mentioning that affective and cognitive empathy are two different aspects and that certain dimensions of empathy might be modulated and improved by personalized intervention strategies [55]. Thus, two recent studies focused on improving cognitive empathy by promoting behaviors related to agreeability, such as patient-centered attention [59,60]. The authors indicated that affective empathy can also be improved by controlling neuroticism and anxiety, especially in medical students with people-oriented specialty preferences [59,60].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth mentioning that affective and cognitive empathy are two different aspects and that certain dimensions of empathy might be modulated and improved by personalized intervention strategies [55]. Thus, two recent studies focused on improving cognitive empathy by promoting behaviors related to agreeability, such as patient-centered attention [59,60]. The authors indicated that affective empathy can also be improved by controlling neuroticism and anxiety, especially in medical students with people-oriented specialty preferences [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, two recent studies focused on improving cognitive empathy by promoting behaviors related to agreeability, such as patient-centered attention [59,60]. The authors indicated that affective empathy can also be improved by controlling neuroticism and anxiety, especially in medical students with people-oriented specialty preferences [59,60]. Therefore, the proper understanding of personality traits in medical students will help educators guide them to better choose a suitable specialty which will definitely result in a major improvement of the patient's outcome and a considerable decrease in the burden on healthcare systems.…”
Section: Discussionmentioning
confidence: 99%
“…Debido al poco tiempo de intervención del que se dispone y, sabiendo que con la privación visual aumenta la empatía hacía la discapacidad visual (Guilera et al, 2017), se considera oportuno aumentar el efecto de la escena cinematográfica que se utilizará con el alumnado en la sesión privando a los estudiantes del sentido de la vista. Previamente, se organiza el espacio del aula de tal manera que la pantalla queda a sus espaldas y se deja sobre las sillas un pañuelo de cuello para que se venden los ojos.…”
Section: Procesounclassified
“…Ahora bien, independientemente de que se trate de una escena o de una película, la investigación dice que la comunicación con el espectador se produce a tres niveles, siendo el primer nivel el de los sistemas perceptivos (Gutiérrez, Pereira y Valero, 2006), de manera que la escena, como material audiovisual que es, nos llega por el medio auditivo y el visual (Cebrián, 1995). A este respecto, existe investigación en el ámbito médico que afirma que el hecho de participar en un contexto sin algún sentido, ocasiona, diferentes tipos de emociones, parece que, ponerse en la piel de la persona con discapacidad, sea ésta auditiva, visual o física, aumenta la empatía hacia dichas personas (Guilera, Batalla y Soler, 2017).…”
Section: Introductionunclassified